Di and tripeptides from marine sources can target adipogenic process and contribute to decrease adipocyte number and functions. (August 2015) - Ben Henda, Yesmine; Laamari, Mariem; Lanneluc, Isabelle; Travers, Marie-Agnès; Agogué, Hélène; Arnaudin, Ingrid; Bridiau, Nicolas; Maugard, Thierry; Piot, Jean-Marie; Sannier, Frédéric; Bordenave-Juchereau, Stéphanie
Highlights: The effect of marine derived cryptides on adipogenesis of human adipocytes was investigated. Marine cryptides ACE-inhibitory activity is not related with adipogenesis. AP, VAP and AKK may inhibit growth of preadipocytes during proliferation stage. GPL and IY down-regulated adipocyte specific differentiation markers. Abstract: The effect of 11 marine-derived cryptides was investigated on proliferation, differentiation and maturation of human white pre-adipocytes (HWP). They were all formerly identified as potent Angiotensin-Converting-Enzyme inhibitors. Val-Trp (VW), Val-Tyr (VY), Lys-Tyr (KY), Lys-Trp (KW), Ile-Tyr (IY), Ala-Pro (AP), Val-Ile-Tyr (VIY), Leu-Lys-Pro (LKP), Gly-Pro-Leu (GPL), Ala-Lys-Lys (AKK) and Val-Ala-Pro (VAP) were previously found in fish products and co-products as well as other marine resources like wakame. Treatment with AP, VAP and AKK greatly affected viability of HWP during the proliferation period while KW and VW treatment reduced the number of viable cells during the differentiation stage. A GPL and IY incubation during the differentiation stage allowed the decrease of their final lipid content, of the GPDH activity and of the mRNA level of adipocyte markers (aP2, GLUT4, LPL and AGT). Moreover, a down regulation of both PPARγ and C/EBPα expression, two key regulators of adipogenesis, was observed. These findings indicate that small bioactive peptides from marine protein hydrolysates can target adipogenesis and thus could regulate energy metabolism disorders.